Positive pathological margins after loop electrosurgical excision procedure – Management and outcome. Issue 5 (May 2023) - Davidesko, Sharon; Meirovitz, Mihai; Shaco-Levy, Ruthy; Wainstock, Tamar; Baumfeld, Yael; Erenberg, Miriam; Sade, Shanny; Kessous, Roy
Abstract: Objective: Pathological involvement of cervical conization margins is a risk factor for recurrence, although management of these patients is controversial. We aimed to define risk factors for positive margins and compare recurrence following additional surgical intervention compared to conservative management. Methods: A retrospective study of all conizations at our center between 2010 and 2019. Univariate analysis identified characteristics associated with positive margins. Women were stratified by mode of management comparing three groups (surveillance, repeat conization or hysterectomy) then two groups (surveillance vs. additional surgery). Kaplan Meyer survival curves compared cumulative recurrence stratified by mode of management. Pathological results of subsequent surgical procedures were examined for residual disease. Results: Of 448 conizations performed, 131 (29.2%) had positive margins which were associated with menopause, high-grade cytology and endocervical gland involvement. Women who underwent surveillance (n = 45) were more likely to be nulliparous, with low-grade histology and less endocervical gland involvement. Women who underwent hysterectomy (n = 61) were more likely to be postmenopausal and parous. Recurrence did not differ significantly in the three-group (p = 0.073) or two-group model (6.4% vs. 7.1% p = 0.869). Kaplan Meyer survival curves depicting cumulative recurrence did not differ significantly in either model (log rank test p = 0.642 for the three-group model, and p = 0.868 for the two-group model). Residual disease was found in 51.6% of hysterectomy specimens and 52.6% of repeat conizations. Conclusion: Surveillance is non-inferior to additional surgery in cases with positive conization margins and constitutes a valid option specifically for younger women at risk of future obstetric complications and those susceptible post-hysterectomy complications.